Sinden-Pangreman Staging Style in Wayang Jek Dong Performance of Pandhawa Laras Group - Tosabila, Inggar Belzky; Sekti, Retnayu Prasetyanti (PT. Hafasy Dwi Nawasena, 2024)
Pandhawa Laras is a group engaged in the field of performing arts, especially East Javanese shadow puppetry (Jek Dong), which was founded on May 13, 2009. Pandhawa Laras means Pan